Examining the Benefits of the 340b Drug Discount Program. Issue 3 (July 2018) - Gerlach, Jarrett; McSweeney, Sarah; Swearingen, Angela; Coustasse, Alberto
Abstract : The 340B Drug Discount Program required drug manufacturers to provide discounted outpatient drugs to health care organizations serving vulnerable patient populations to allow these institutions to offer more services to more people. As the 340B program expanded, controversy centered on which entities have benefited from the program. Many health care organizations sold 340B drugs to well-insured patients at full price and have thus been financially rewarded. Amendments to the program have permitted 340B providers to use contract pharmacies to dispense 340B medications, furthering the debate over which stakeholders are benefiting from the program. The purpose of this study was to determine which stakeholders benefited because of the 340B Drug Discount Program and what have been the drivers of recent changes to the program. The study used a literature review. One database aggregator and six academic databases were used to collect 70 total sources. These sources were reviewed and reduced to 39 sources, which were used in the written research. Of these, 20 sources were used in the Results section. Research showed that 340B eligible entities and contract pharmacies have financially benefited from the 340B program. Patient benefit has been indirect, as qualified providers have expanded service offerings and increased access to health care services. Regulatory reform, as well as profit potential, has driven the expansion of 340B as more providers have expanded eligible service lines. Although the goal of the 340B program has often been misconstrued, direct financial benefits to eligible providers have allowed for this expansion of access.